The Development of Calculating Work Volume Learning Video in the Implementation of Building Construction - Nurfitriyani, Sintya Andryati; Kusumawardani, Rini; Sutopo, Yeri (Journal of Vocational and Career Education, 2021)
The lack of learning media regarding the Bill of Quantity of Building Construction, Sanitation, and Maintenance reduces students' understanding of the learning material in calculating the work quantity in building construction process. It results in unsatisfactory students learning outcomes.The use of learning media in accordance with technological developments is expected to be a breakthrough to increase the students’ interest. This study aims to develop a video-based learning media to calculate the work quantity in building construction and to analyze its effectiveness. The research method used was Research and Development with the ADDIE approach. This study used the intraclass correlation coefficients method assisted by SPSS v.19 software to analyse the adequacy and practicality validation and used the t-test to analyse the effectiveness of the video learning. The results of the development and data analysis of the video learning were stated by the content experts with a score of 4.03 (adequate) and by the media experts with a score of 4.28 (very adequate). From the practical aspect, the learning video was tested by the students with a reproducibility coefficient score of 0.9 (very practical). The data analysis results of the effectiveness test showed that the average N-Gain score for the experiment class was 56.73% (quite effective). The results of the t-test showed a significant difference between before and after using the video learning, with an increasing score of 11.23. Based on the results of the study, it can be concluded that the video learning is very adequate, very practical, and quite effective to increase the students’ competence on the work quantity calculation in building construction.